10 Things You Should Not Forget When Adapting a Test Into Spanish <subtitle>A Practical Decalogue</subtitle> - Ricardo Rosas; Marcelo Pizarro; Victoria Espinoza (Psychological Test Adaptation and Development, 2024)
Abstract: Adapting a test from one language to another is no easy task. The literal translation of the items is certainly not enough since the meanings and references change from one language to another. In the case of Spanish adaptations, the problem becomes even more complex, as there are many varieties of Spanish, almost as many as Spanish-speaking countries. This article presents 10 tips for adapting tests to Spanish regarding the morphological, syntactic, and pragmatic elements that should be considered when adapting an instrument to Spanish. These tips are based on experience with the adaptation of various instruments, such as the Wechsler Intelligence Scales (WISC-III, WAIS-IV, and WISC-V) and the Big Five from English, and the ELFE scale, MARKO-D, and the Berlin Intelligence Test from German.